Design Guidelines for Energy Efficient AC to DC Power Supplies - Chrysostomou, Michael; Christofides, Nicholas; Ioannou, Stelios; Marouchos, Christos (My University, 2021)
Data processing for Internet of Things (IoT), and Internet and Communications Technologies (ICT), is increasing with unpresented rates, something that has led to an increased requirement for Power Supply Units (PSU). A respectful 1% of global energy consumption is due to data processing in datacenters. The global datacenter energy consumption is rising the last few years due to the 5G technology and the low latency and high-speed requirements. In the same manner IoT applications, and energy industries are rising, and is estimated that an impressive 70% of global energy is passing through converters such as PSUs. This work analyses the main constituent components in each individual conversion stage of a PSU and proposes the most appropriate designs for higher efficiency. The theoretical analysis is verified by simulations using the PSIM Thermal Module. Finally, this paper suggests techniques and trade-offs that must be exploited for the optimized PSU design with higher energy efficiency under varying parameters.
Keywords: Power Supply Units (PSU); Converter; Energy; Efficiency